Digital sociology and new opportunities for social and educational rehabilitation of disabled people - S. V. Kibakin; Y. A. Malakhova (Цифровая социология)
Based on the conducted sociological research and using modern methodological approaches of digital sociology, the feasibility of developing institutional conditions for improving the educational rehabilitation of disabled people by means of modern Internet technologies has been justified. Examples of the development of analogical problems in the works of domestic and foreign authors have been given. The possibilities of scientific and methodological support of social experiments on the development and implementation of educational Internet communications to overcome the disability of disabled people using the Arsenal of digital sociology have been described separately. The data on the attitude of disabled people to higher education in the system of their rehabilitation and life activity, with the identification of social groups with positive, uncertain and negative attitudes with a predominant positive attitude to the possibility of educational rehabilitation have been provided. The educational needs of people with disabilities in various areas have been described, their quantitative characteristics with the definition of priorities and areas of education that are not relevant for people with disabilities have been presented. A significant place in the article has been given to the possibilities of involving disabled people in the process of developing educational programs and in research activities, both in terms of the availability of willing people among them, and the use of various forms of their integration into real research projects as part of temporary creative teams. The conditions for the implementation of scientific support for the development of training programs in the Internet space by conducting their practical testing on the example of the Zagorsk experiment have been characterized separately. Attention to supporting individual research projects of people with disabilities in the course of higher education has been paid, ways to help them collect experimental material have been substantiated. Separately, the role and place of joint forms of scientific activity of disabled people, teachers and students in the performance of state tasks have been shown. Taking into account the important role of social inclusion of disabled people in Internet communications, the prevalence of creating accounts in the Internet information and communication network and using various Internet resources among disabled people and family members has been separately reflected.